2020
DOI: 10.1002/prp2.601
|View full text |Cite
|
Sign up to set email alerts
|

Gut bacterial microbiome composition and statin intake—A systematic review

Abstract: Recently, the gut microbiome has become an important field of interest. Indeed, the microbiome has been associated to numerous drug interactions and it is thought to influence the efficacy of pharmacologic treatments. Although statins are widely prescribed medications, there remains considerable variability in its therapeutic response. In this context, we aimed to investigate how statins modulate the gut microbiome and, reversely, how can the microbiome influence the course of anti‐hypercholesterolemic treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 61 publications
(80 reference statements)
0
25
0
Order By: Relevance
“…Lastly, recent post hoc analyses of randomized trials of patients with UC and NSCLC showed worse OS and progression-free survival in individuals in the ICI arm (the anti-PD-L1 atezolizumab) receiving ATBs but not in those in the control arm (conventional chemotherapy) receiving ATBs. 23,24 Along with ATBs, a number of other drug classes can induce dysbiosis: proton pump inhibitors (PPIs), drugs for functional gastrointestinal disorders (particularly phloroglucinol), anti-vitamin K (AVK) anticoagulants, antiarrhythmics, nonsteroidal anti-inflammatory drugs (NSAIDs), vitamin D3 (known for its protective role in intestinal homeostasis), 25 metformin (which stimulates the gut microbiota and the immune system), 26 opioids, statins (which appear to be associated with an anti-inflammatory gut microbiotic profile), 27 levothyroxine, and psychotropics. [28][29][30][31][32][33][34][35] The objective of the present study was to evaluate the associations between ATBs (especially amoxicillin and amoxicillin/clavulanic acid) and other drugs known to modify gut microbiota on one hand and OS and the tumor response in patients treated with ICIs (particularly patients with melanoma) on the other.…”
Section: Associations Between Dysbiosis-inducing Drugs Overall Survival and Tumor Response In Patients Treated With Immune Checkpoint Inhmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, recent post hoc analyses of randomized trials of patients with UC and NSCLC showed worse OS and progression-free survival in individuals in the ICI arm (the anti-PD-L1 atezolizumab) receiving ATBs but not in those in the control arm (conventional chemotherapy) receiving ATBs. 23,24 Along with ATBs, a number of other drug classes can induce dysbiosis: proton pump inhibitors (PPIs), drugs for functional gastrointestinal disorders (particularly phloroglucinol), anti-vitamin K (AVK) anticoagulants, antiarrhythmics, nonsteroidal anti-inflammatory drugs (NSAIDs), vitamin D3 (known for its protective role in intestinal homeostasis), 25 metformin (which stimulates the gut microbiota and the immune system), 26 opioids, statins (which appear to be associated with an anti-inflammatory gut microbiotic profile), 27 levothyroxine, and psychotropics. [28][29][30][31][32][33][34][35] The objective of the present study was to evaluate the associations between ATBs (especially amoxicillin and amoxicillin/clavulanic acid) and other drugs known to modify gut microbiota on one hand and OS and the tumor response in patients treated with ICIs (particularly patients with melanoma) on the other.…”
Section: Associations Between Dysbiosis-inducing Drugs Overall Survival and Tumor Response In Patients Treated With Immune Checkpoint Inhmentioning
confidence: 99%
“…Along with ATBs, a number of other drug classes can induce dysbiosis: proton pump inhibitors (PPIs), drugs for functional gastrointestinal disorders (particularly phloroglucinol), anti-vitamin K (AVK) anticoagulants, antiarrhythmics, nonsteroidal anti-inflammatory drugs (NSAIDs), vitamin D3 (known for its protective role in intestinal homeostasis), 25 metformin (which stimulates the gut microbiota and the immune system), 26 opioids, statins (which appear to be associated with an anti-inflammatory gut microbiotic profile), 27 levothyroxine, and psychotropics. 28 35 …”
Section: Introductionmentioning
confidence: 99%
“…The gut microbiota is the largest reservoir of microorganisms (bacteria, archaea, viruses, and fungi) inhabiting the human body [ 1 , 5 ]. The intestinal bacteria in healthy subjects primarily consists of Actinobacteria, Firmicutes, Proteobacteria , and Bacteroidetes [ 11 ], while the colon harbors bacteria of the Bacteroidaceae, Prevotellaceae, Rikenellaceae, Lachnospiraceae , and Rumniococcaceae families [ 12 ].…”
Section: Gut Microbiota In Sars-cov-2 Infectionmentioning
confidence: 99%
“…Genetic data indicate that the human body contains only 1% of human genes, and 99% of the genes belong to the microorganisms that inhabit the host [ 4 ]; therefore, the gut microbiome of an individual can encode more than 150 times more genes than the host genome. In contrast to the host genome, the quantitative and qualitative composition of microbiota is dynamic and changes under the influence of environmental factors, including the diet, exposure to antibiotics and, in particular, in response to disease [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Microbiota denotes the entire population of microorganisms that colonizes a specific region, including not just bacteria but also other microbes such as fungi, protozoans, viruses, and archaea ( 37 , 38 ). The majority of microorganisms residing in humans are found in the gut, forming the largest microbial ecosystem of the body.…”
Section: Effects Of Periodontal Pathogens On Intestinal Microbial Barriermentioning
confidence: 99%